DOI: 10.29007/5w82
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Dynamic 3-D Models in Construction Management Courses

Abstract: The traditional lecture method is commonly used to teach Construction Management students. But most of the construction management concepts are hard to convey using this method, and students face obstacles to learning some of the ideas due to the difficulties in visualizing the concepts learned. This research aims to evaluate the influence of using three-dimensional models (3D) as a visualization tool in the construction management undergraduate program. The technique was implemented in three courses at differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…However, Ghanem (2021) reported that only fifty percent of the surveyed students in the estimating course thought that the 3D modeling helped them. Therefore, the study concluded that the usage of 3D models in estimating course was less effective in students learning than in materials & methods and construction graphics course.…”
Section: D Bim Models In Cm Coursesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Ghanem (2021) reported that only fifty percent of the surveyed students in the estimating course thought that the 3D modeling helped them. Therefore, the study concluded that the usage of 3D models in estimating course was less effective in students learning than in materials & methods and construction graphics course.…”
Section: D Bim Models In Cm Coursesmentioning
confidence: 99%
“…While 3D BIM models have been adopted and used in many CM courses, only two existing studies (Gier, 2008 andGhanem, 2021) have explored the effectiveness of 3D BIM models in estimating courses. Based on the results from the two studies, it is not clear if using 3D BIM models in estimating course is effective or helpful in performing quantity takeoff and estimating.…”
Section: Research Objective and Questionsmentioning
confidence: 99%
See 1 more Smart Citation